SETTLEMENT OF TRADEMARK DISPUTE - Giezka Juninta Ryhilda, Etty Susilowati *), Rinitami Njatrijani (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2013)
Brandis is essentially a sigh that is placed on a product. In order to be accepted as a sigh of the brand, then it must have a distinguishing power and aquality in essence, that has the ability to be used as a sign that can distinguish by individuals or a group of people or legal entities that can provide consistent quality assurance. Brand can be disputed if it doesn’t meet the above elements, as in the case of the PT SINAR AGUNG MAKMUR SENTAUSA with PT. SARI AGUNG, PT. JAYA MITRA and PT. CITRA RASA UTAMA taste resolved through the Commercial Court Deasion Nomor 82/Merek/2003/PN.Niaga/Jkt.Pst. Plaintiff’s claim is the paekaging in the process of the commercial court judge didn’t accept the entire complaint filed by plaintiff because defendants have the right exception and argued, so that there is no legal certainty who is entitled to the brand of “SA”. The decision of judge imposes only to the plaintiff to pay the court fee of Rp. 5.000.000 (five million rupiah).